Modelling and simulation for logistic service company : case study on customer service operation - Chow, Deborah Yen May (2014)
Modelling and simulation approach is widely used in the management, manufacturing and services industries. The purpose of using modeling and simulation is to improve in business performance and achieve in business goals and targets. However, there is lack of such an application in the customer service operation for the logistic industry. The project is performed to evaluate the roles and responsibilities of Customer Service Officer (CSO) in the import and export operations for a logistic service company, to ensure customer satisfaction for the services provided by CSO from a logistic service company in the import and export operations and to recommend appropriate parameters for a logistic service company for improvement of business performance after operation re-engineering. The research method consists of interview, observation, document review and simulation. The project was conducted in DNE group, a logistic service company located in Klang Valley, Malaysia. The general manager and CSO of import and export operation (five CSO for each operation) were interviewed. The work of CSO of both import and export operations were observed. The relevant forms for the import and export operations and the CSO import and export operational procedure where the company intends to adhere to ISO 9001:2008 were reviewed. ARENA simulation was used to simulate the suggested methods for the purpose of improving business performance. There are four proposals for the import operation. The proposals are to add two working hours for each CSO, to add an extra officer to each import process, to allow two shifts for the CSO and to have more job separation. The export operation consists of three proposals. The proposals are to add two working hours for each CSO, to add an extra officer to each export process and to allow two shifts for the export CSO. These suggestions can be applied to other logistical companies and a conceptual model can be established for future research.